Factors Causing Ineffectiveness of Capex-Opex Management on the Reliability of Coal-Fired Power Plants - Fachrudin, Mohammad Anang; Gunarta, I Ketut (MALCOM: Indonesian Journal of Machine Learning and Computer Science, 2026)
This study examines the ineffectiveness of Capital Expenditure (Capex) and Operational Expenditure (Opex) management in improving the reliability of coal-fired power plants in isolated electricity systems, using PLTU Bolok and PLTU Ropa in East Nusa Tenggara as case study units. The study is motivated by fluctuations in Equivalent Availability Factor (EAF) and Equivalent Forced Outage Rate (EFOR) during 2019-2024, despite recurring maintenance and investment expenditures. A descriptive case-study design was applied, combining reliability and maintenance performance analysis with Root Cause Analysis (RCA) using a Fishbone Diagram, Pareto Analysis, and Five Whys. The dataset includes Capex and Opex realization, FOH, POH, downtime, maintenance backlog, and the composition of preventive and corrective maintenance. The findings show that ineffective Capex-Opex management is primarily driven by equipment degradation, maintenance delays, high backlog levels, delays in spare-part procurement, delayed critical investments, and the dominance of corrective maintenance. The novelty of this study lies in integrating cost-allocation evaluation, reliability indicators, and root-cause diagnosis into a single analytical framework for isolated coal-fired power plant systems. In practice, the results imply that reliability improvement should prioritize reliability-based maintenance planning, backlog reduction, control of critical-spare procurement, and Capex prioritization based on asset criticality rather than budget magnitude alone.